Pacific youth in agriculture strategy 2011 – 2015 : echoing the voices of young people - Secretariat of the Pacific Community (SPC, 2010)
The findings and recommendations of this strategy suggest the need for a more concerted effort at the family, community, national and regional level to support the development of young people and encourage their participation in agricultural activities and enterprises...